The early history of Blythswood Missionary Institution - Rodger, Alastair (Rhodes University, Faculty of Divinity, Department of Divinity, 1977)
The Mfengu, or Fingos, of the Transkei were a mixed group of refugees. Originally driven from Natal during the Mfecane, they moved into the Transkei and then the Ciskei. In the 1860's some were allowed by the Cape government to settle in an area in the Western Transkei which it had recently seized. The majority of those who moved were opposed to mission work and education. When therefore the government agent for Fingoland, Captain Blyth, and a Free Church of Scotland missionary, Richard Ross, gained the support of a few headmen for an educational Institution in the Transkei, and approached Dr James Stewart of Lovedale to found such an Institution on the lines of Lovedale, they had very slender support. Mfengu subscribe Â£10.00 towards the cost. Stewart agreed on condition the support for this somewhat startling and, to some, unpalatable request was gained mainly because it was known that the government intended introducing a hut tax which would be far more onerous than the levy which, it was estimated, would be required to find the sum Stewart was asking. Blyth was able to use the agreement to a voluntary levy for an institution to persuade the government to postpone the tax. The Institution was built on a larger scale than had been planned, for the Mfengu made two subscriptions, each larger than the total requested, and Stewart raised money in Scotland.
Keywords: Blythswood Missionary Institution -- History